Troubleshooting questions - Lomas, Brian (Successful Presentations, 2009)
Several questions on developing a successful presentations are answered. If you know on how to develop a script, at some point, you will be asked to make a presentation on a given topic, then prepare it in advance. However, if you are asked to present on a subject for which you cannot do any advance preparation, you have two choices -- agree a low-expectancy primary aim or refuse to present on the basis that you will not be able to achieve the required outcome. Short of refusing to do the presentation, start by researching the background to the subject and why the message needs to be delivered. You could ask yourself a question to get things started using the likely questions you had pre-prepared to answer, but ensure you give some new information in your answer as an incentive to the audience to seek more information.